Kesehatan mental pria PSK (Pekerja Seks Komersial): Penderita HIV/AIDS di Indonesia - Rifa’ah, Hana Meliana (Maliki Interdisciplinary Journal, 2024)
HIV has always received attention from many groups including commercial sex workers. The Ministry of Health noted that HIV sufferers are more men than women with a ratio of 75 to 25: 25. Some men have been confirmed to be Commercial Sex Workers who not only serve women but also serve male guests. They usually have back or anal intercourse. The relationship is known as Male Sex Male (MSM). A study published in the international journal of epidemiology revealed that the risk of HIV transmission through anal sex is 18% higher when compared to vaginal penetration. Anal intercourse through the rectum is most at risk of HIV infection because the layer is very thin so it is very easy to damage during sex (Wardani et al., 2020). This study explores the psychosocial experiences of prostitutes with HIV/AIDS, which include individual mental health. The results show that HIV and AIDS cause various mental health problems such as fear, despair accompanied by prejudice against other people’s discrimination, and then psychological pressure felt by male sex workers. Men who like to have sex with other men are already psychologically disturbed. It is important to prevent the factors that can lead to the psychological disruption of MSM before or after being infected with HIV/AIDS. Because prevention is better than cure.